1999
DOI: 10.1136/gut.45.1.129
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of the causes of notably raised aspartate aminotransferase of liver origin

Abstract: Background and aims-To ascertain the causes of raised aspartate aminotransferase (AST) presumed to be of hepatic origin in two hospitals and the local community served by a centralised biochemistry laboratory. Methods-From June 1996 to February 1997 all patients with AST greater than 400 U/l were identified by the biochemistry laboratory; the patients' clinical records were studied to determine the diagnosis, the clinical outcome, and whether the raised AST and its significance had been noted. Results-A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
98
1
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(114 citation statements)
references
References 7 publications
10
98
1
3
Order By: Relevance
“…This protection mechanism provides resistance for the liver against alloxan-induced damage, through hepatic regeneration stimulation and liver lipid peroxidation inhibition (18). The increased plasma AST and ALT levels indicated that diabetes may induce hepatic dysfunction, as supported by previous findings of necrotic livers (19). Therefore, the increased transaminase activity in plasma may be mainly due to the leakage of these enzymes from the liver (20).…”
Section: Discussionsupporting
confidence: 55%
“…This protection mechanism provides resistance for the liver against alloxan-induced damage, through hepatic regeneration stimulation and liver lipid peroxidation inhibition (18). The increased plasma AST and ALT levels indicated that diabetes may induce hepatic dysfunction, as supported by previous findings of necrotic livers (19). Therefore, the increased transaminase activity in plasma may be mainly due to the leakage of these enzymes from the liver (20).…”
Section: Discussionsupporting
confidence: 55%
“…For example, about 60% of cases of elevated hepatic AST levels in Wales can be attributed to ischemic or toxic liver injury, 10 whereas orofecal transmittable hepatitis viruses are the major cause (> 60%) of sporadic acute and fulminant hepatitis in the Far East. 11 The incidence of primary biliary cirrhosis ranges from 1.9-2.2 per 100 000 in Australia to 0.34-0.42 per 100 000 in Asia, 12 and the prevalence of homozygosity for the C282Y mutation in the HFE gene can be found in about 5 per 1000 people of northern European descent 13 but 0.0001 per 100 people of African American ethnicity.…”
Section: Wherementioning
confidence: 99%
“…Ischemic and hypoxic acute liver damage is more likely in patients with concomitant clinical conditions such as sepsis or low-flow hemodynamic state. 10,28,30 Careful investigation of the patient's pharmacologic history is essential in order to identify medications and herbal products associated with hepatotoxicity. 16,17,35 Acetaminophen-induced hepatic damage causes 54% and 16% of the cases of acute liver failure in the United Kingdom and United States respectively.…”
Section: Marked and Moderate Aminotransferase Increasementioning
confidence: 99%
“…Acute pure cytolytic syndrome is characterized by severe increases in aspartate and alanine aminotransferases, with normal or moderately abnormal gamma-glutamyl transpeptidase. 5 Although microbiological data was uninformative, clinical and laboratory data suggest that the cytolysis was due to an infection.…”
Section: Discussionmentioning
confidence: 99%